Turak Ngurah Ocin sebagai Ide Dasar Penciptaan Tari Kreasi - Beny Olala, Numeri; Astuti, Andi Arie; Grindraswari, Nawung Asmoro (FKIP, Universitas Palangka Raya, 2025)
Turak Ngurah Ocin is a dance creation that aims to preserve and introduce the culture of the Dayak Ngaju Ot Danum community through the representation of traditional women's activities in fishing using fishing gear such as buwu and takalak. The dance creation method used in this work includes three stages, namely exploration, improvisation, and forming. The exploration stage is carried out by collecting data through observations and interviews to develop dance concepts. In the improvisation stage, the stylist tries various possibilities of movement based on experiences and emotions related to traditional activities. Furthermore, in the forming stage, the improvised movements are arranged into a complete and meaningful dance composition. The result of this process is a 12-minute dance performance that emphasizes aesthetic, educational and local cultural values. This performance is a medium of artistic expression as well as a means of preserving Dayak culture for the younger generation. Recommendations from this work are the importance of applying structured creation methods and exploring local culture as inspiration in the development of performing arts.